Effect of mu Agonists on Long-Term Survival and Recurrence in Nonsmall Cell Lung Cancer Patients. Issue 33 (August 2015) - Wang, Kai; Qu, Xiao; Wang, Ying; Shen, Hongchang; Liu, Qi; Du, Jiajun; Tuomo, Rantanen.
<x xml:space="preserve">Abstract</x> Abstract Opioids are widely used for postoperative analgesia. Morphine may have an effect on cell replication, migration, and cancer recurrence. However, the association of postoperative mu agonists with outcome of nonsmall cell lung cancer (NSCLC) patients has not been fully investigated. We retrospectively evaluated the impact of postoperative mu agonists on overall survival (OS) and disease-free survival (DFS) in early stage NSCLC patients. Patients and relevant medical information were selected from the Bio-Bank of Shandong Provincial Hospital. Difference of clinicopathologic information in postoperative mu agonists group and no mu agonists group was analyzed by χ2 test. Univariate and multivariate Cox regression analysis were conducted and represented as hazards ratio and 95% confidence interval form. The primary endpoint was OS and secondary endpoint was DFS. This retrospective study included 984 consecutive NSCLC patients who underwent surgery between January 2006 and December 2011. No significant difference existed between postoperative mu agonists usage group and no mu agonists usage group in clinicopathologic information except operation type (P = 0.041). Postoperative mu agonists usage was related to shorter OS (HR 1.514, 95% CI 1.197–1.916, P = 0.001) and shorter DFS (HR 1.415, 95% CI 1.123–1.781, P = 0.003) in the multivariate Cox regression model. For the patients who received postoperative chemotherapy or radiotherapy postoperative mu agonists also predict shorter survival (HR 1.437, 95% CI 1.041–1.982, P = 0.027). Subgroup analysis showed that administration of postoperative mu agonists was related to shorter OS, especially in males, more smoking, poor differential degree, bilobectomy or pneumonectomy, and stage III subgroup, respectively. Administration of postoperative mu agonists was related to shorter OS and DFS for the NSCLC patients who underwent surgery.